Discriminatory rapid tests cause HIV-type misclassification—evaluation of three rapid tests using clinical samples from Guinea-Bissau. (4th June 2019) - Hønge, Bo Langhoff; Jespersen, Sanne; Medina, Candida; Té, David da Silva; da Silva, Zacarias José; Christiansen, Mette; Kjerulff, Bertram; Laursen, Alex Lund; Wejse, Christian; Krarup, Henrik; Erikstrup, Christian; ,
Abstract: Background: Discrimination among HIV types is important because HIV-2 is naturally resistant to some of the first-line drugs used in the treatment of HIV-1. We evaluated three assays for HIV-type discriminatory capacity: SD Bioline HIV 1/2 3.0 (Bioline), First Response HIV 1-2-0 Card Test (First Response) and Genie III HIV-1/HIV-2 (Genie III). Methods: Based on results from the Bioline assay, samples from 239 HIV-infected patients from the Bissau HIV cohort in Guinea-Bissau were retrospectively selected for evaluation. Genie III and First Response were scored by three independent readers and compared with a reference test (INNO-LIA HIV I/II Score) confirmed by HIV RNA as well as DNA detection. Results: The best performing test was Genie III, with an average agreement with the reference test of 93.4%, followed by First Response (86.1%) and Bioline (72.4%). First Response and Bioline were scored with a false high number of HIV-1/2 dual infections. For both First Response and Genie III, there were discrepancies among independent readers, and some tests were scored as HIV non-reactive. Conclusions: Using these rapid tests with a suboptimal performance will presumably result in a high rate of false HIV-1/2 dual diagnoses, depriving patients of alternative treatment options in cases of treatment failure.